Neutron Diffraction Study of Multiferroic 0.6NiFe2O4/0.4BaTiO3 Composite - Sukirman, Engkir; Sarwanto, Yosef; Ahda, Syahfandi; Insani, Andon (UI Scholars Hub, 2019)
Neutron diffraction study on the 0.6NiFe2O4/0.4BaTiO3 multiferroic composite has been carried out. The 0.6NiFe2O4/0.4BaTiO3 multiferroic composites have been synthesized by solid reaction method. In this study, 20 g of BaTiO3 (BTO) and 20 g of NiFe2O4 (NFO) compounds were prepared from the powder raw materials of BaO3 and TiO2 for BTO, and NiO and Fe2O3 for NFO. Furthermore, both BTO and NFO were each crushed for 5 hours using High Energy Milling (HEM). Then the BTO and NFO were calcined in the furnace at 950 °C/5 hours and 900 °C/5 hours, respectively. Both NFO and BTO precursors were manually mixed with a weight percent ratio of NFO:BTO was 100:0, 60:40, and 0:100, hereinafter referred to NFO, NFO/BTO, and BTO, respectively. Then the three samples were pressed into pellets. The pellets were then sintered at 1150 °C/5 hours with a heating rate of about 44.8 °C/min. Once cooled to room temperature within the furnace it was obtained NFO, BTO, and NFO/BTO multiferroic composite. The magnetic properties of the material were observed with the aid of the Vibrating Sample Magnetometer (VSM) instrument. The nuclear structure of BTO, and the magnetic structure of NFO, and NFO/BTO multiferroic composite were determined by neutron diffraction technique using the high resolution powder neutron diffractometer. The cations arrangement of NFO was obtained by whole pattern fitting with the Rietveld method based on neutron diffraction data using FullProf software. The cations arrangement was obtained by refining the occupancy of individual cation at tetrahedral and octa-hedral sites. The results of the analysis show that both NFO and 0.6NFO/0.4BTO samples have a mixed spinel structure, it means that there are cations of Ni2+ and Fe3+ on A-site and B-site. In NFO sample, the cations distribution among the A-site and B-site of NiFe2O4 is [Ni0.002Fe0.852][Ni0.006Fe0.862]2O4. The cations distribution among the A-site and B-site of NiFe2O4 in 0.6NFO/0.4BTO samples is [Ni0.0250Fe0.8975] [Ni0.012Fe0.950]2O4. So, the effect of adding BTO as a composite is to increase Ni2+ occupancy by 12.5 times on A-site and 2 times on B-site. The magnetic moment of mul-tiferroic 0.6NFO/0.4BTO composite is 2.4(5) μB same as one of NFO. The BTO content in the composite has caused ten-sile strains induced into the NFO lattice, and at the same time, tensile strains of NFO caused the compressive strain on the c lattice of BTO even though the unit cell volume of BTO is also increasing from 64.100(5) to 64.374(6) Å3.